Spinoza. - Jarrett, Charles (Guides for the perplexed., 2007)
Continuum's Guides for the Perplexed are clear, concise and accessible introductions to thinkers, writers and subjects that students and readers can find especially challenging. Concentrating specifically on what it is that makes the subject difficult to fathom, these books explain and explore key themes and ideas, guiding the reader towards a thorough understanding of demanding material. Benedict de Spinoza is a major philosopher of enduring influence and importance, whose work is encountered by all serious students of Western philosophy; his Ethics is one of the seminal works of moral, relig.